Library Networks and Library Legislations: A Comparative Study of State Library Legislations of India - Gopinath, M. A. (Journal of Information and Knowledge, 1981)
Presents chronological movements of legislation programmes for establishing library systems throughout the world. Discusses the good and bad features of the four library acts of India-namely, Tamil Nadu (1948), Andhra Pradesh (1953), Karnataka (1965) and West Bengal (1980). The network structure, the governance problems, and the library finances aspects of these state acts are compared.